Impact of the corticosteroid indication and administration route on overall survival and the tumor response after immune checkpoint inhibitor initiation. (February 2021) - Gaucher, Louis; Adda, Leslie; Séjourné, Alice; Joachim, Camille; Chaby, Guillaume; Poulet, Claire; Liabeuf, Sophie; Gras-Champel, Valérie; Masmoudi, Kamel; Moreira, Aurélie; Bennis, Youssef; Batteux, Benjamin
Background: Based on their indications, systemic corticosteroids appear to negatively affect clinical outcomes in immune checkpoint inhibitor (ICI)-treated patients. There are few data on the influence of topical and inhaled corticosteroids on the ICIs' effectiveness. Methods: In a single-center study, we retrospectively investigated the impact of systemic corticosteroids according to their indication [an immune-related adverse event (irAE) or another indication] on overall survival (OS) and the tumor response in all consecutive patients after initiation of ipilimumab, nivolumab or pembrolizumab over a 9-year period. The impacts of topical and inhaled corticosteroids were also examined. Results: Three hundred and seventy-two patients were included. The mean ± standard deviation age was 64.0 ± 12.1 years. The most frequently prescribed ICI was nivolumab (in 58.3% of the patients) and the most frequent indications were lung cancer (44.6%) and melanoma (29.6%). Systemic corticosteroid use for an irAE did not have a negative impact on OS [adjusted hazard ratio (HR) [95% confidence interval (CI)] 1.04 (0.56–1.95), p  = 0.902] or the best overall tumor response [adjusted odds ratio (OR) (95% CI) 1.69 (0.52–6.56), p  = 0.413], while systemic corticosteroid use for another indication was associated with shorter OS [adjusted HR (95% CI) 1.34 (1.05–2.03), p  = 0.046] and a poor best overall tumor response [adjusted OR (95% CI) 2.04 (1.07–5.80), p  = 0.039] with a cumulative dose cut-off of 3215 mg prednisolone equivalent (specificity 71.4%; sensitivity 65.3%) and a time cut-off of 132 days (specificity 71.4%; sensitivity 89.8%). The use of topical corticosteroids was associated with a longer OS; this was probably due to dermatological irAEs. Inhaled corticosteroid use did not influence OS. Conclusion: Systemic corticosteroid use for an irAE does not impact OS or the tumor response, whereas use for other indications (themselves often associated with a worse prognosis) does. Topical and inhaled steroids do not have a negative impact on OS.